25 Shotokan Kata - Fernández Rincón, Martín M. (Revista de Artes Marciales Asiáticas, 2012)
Albrecht Plfüger. Barcelona Paidotribo, 2006 (3ª ed.). 84 páginas. <span style="mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: IT; mso-bidi-font-weight: bold;" lang="IT">21x27,5 cm. I.S.B.N.: 978-84-8019-460-0.